Effect of Recycled Concrete Aggregates on Plain Concrete Compressive Strength and its Environmental Sensitivity. - Mugisha, Elaijah (Kabale University, 2025)
This research aimed to establish the effect of recycled concrete aggregates on plain concrete compressive strength and its environmental sensitivity. It was guided by objectives that involved comparing the properties of RCAs and NCAs, to develop an optimal concrete mix design that incorporates RCAs, determining the optimal percentage ratio of RCA that maximizes compressive strength and environmental sensitivity, and finally determining the physical properties of concrete produced (fresh and hardened state). Mainly the research was about the compressive strength of plain concrete using recycled concrete aggregates. The concrete was designed to have a 25MPa compressive strength and slump range of (25-75) mm. The ratios of replacing natural aggregates with recycled concrete aggregates were 0%, 20%, 40%, 60%, and 100%. The test samples were crushed to determine their compressive strength values after 7, 14, and 28 days of curing. Other test samples were exposed to environmental factors after 28 days of curing for instance elevated temperature (1 hour, @105 ℃ ), humidity, and rainwater for 14 days and compressed to note the change in compressive strength of natural concrete and recycled concrete and results showed that recycled concrete is more affected by environment factors than natural concrete made with virgin aggregates. The results showed that slump decreases with an increase in replacement percentages and also strength reduces with an increase in replacement ratio. From the experimental results of this study, the optimal replacement percentage should be 24.7%.